Check On Level Of Environmental Contamination By Mercury And Cleanup Of Abetina Mining Area (Grosseto-Italia) - G. Belardi (The Minerals, Metals and Materials Society, 1996)
The purpose of the study was to check on the level of environmental contamination and to design a project for cleaning up the Abetina Mine area at Piancastagnaio (Grosseto, Italy). Contamination of this area had occurred during the mining and treatment of cinnabar (HgS) over a prolonged period. The aim of the project is to remove the sources of contamination or render them harmless. Mining of the Piancastagnaio deposit started in 1840, mercury metal being extracted from the ore by thermal treatment. Together with Spain, Italy was the first country to produce this metal and was the world leader in this field between 1936 and 1943. Though mercury production in the Monte Amiata region of Tuscany ceased in 1974 the ensuing environmental impact is very evident, taking the form of rusty old mining and processing works, plus waste tips which still contain considerable amount of mercury even after the ore had been subject to thermal extraction treatment. The research which has been conducted included mapping the area to identify the main sources of mercury and arsenic pollution, as well as the level of environmental contamination. Mercury and arsenic values in excess of 16,000 and 150 ppm respectively are encountered in the most highly-contaminated places. The cleanup project has been drawn up on the basis of the field and laboratory investigations. This provides for a combination of remediation measures on the land concerned, as well as in situ inertization of contaminating elements by means of mixtures of chemical compounds such as cyclosiloxanes. Due account has been taken of Italian and EU environmental regulations when establishing the measures for rendering the various polluting element innocuous. 'The efficacy of the inertization techniques has been checked by yield tests in acetic acid and carbon dioxide, reducing the Hg and As contents of the material in the untreated and treated states from maximum values of 7 mgll to minima close to zero.